2018
DOI: 10.3390/app8112288
|View full text |Cite
|
Sign up to set email alerts
|

Markov Chain Investigation of Discretization Schemes and Computational Cost Reduction in Modeling Photon Multiple Scattering

Abstract: Establishing fast and reversible photon multiple scattering algorithms remains a modeling challenge for optical diagnostics and noise reduction purposes, especially when the scattering happens within the intermediate scattering regime. Previous work has proposed and verified a Markov chain approach for modeling photon multiple scattering phenomena through turbid slabs. The fidelity of the Markov chain method has been verified through detailed comparison with Monte Carlo models. However, further improvement to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To further demonstrate the error from the Markov chain approximation, we incorporated the relative error of each model, as shown in Figure 3. As we introduced in our previous work [17], the Markov chain model had the worst performance near 90 • , around which the signal was hard to capture by the sensors in the experiments. Therefore, in Figure 3, we just compared the results at 135 • (corresponding to the maximal point in 90 • -180 • ) to demonstrate the error of the time-based model, and we also confirmed that this error was representative of the overall error of the Markov chain models.…”
Section: Numerical Verification Against Monte Carlo Simulationsmentioning
confidence: 96%
See 3 more Smart Citations
“…To further demonstrate the error from the Markov chain approximation, we incorporated the relative error of each model, as shown in Figure 3. As we introduced in our previous work [17], the Markov chain model had the worst performance near 90 • , around which the signal was hard to capture by the sensors in the experiments. Therefore, in Figure 3, we just compared the results at 135 • (corresponding to the maximal point in 90 • -180 • ) to demonstrate the error of the time-based model, and we also confirmed that this error was representative of the overall error of the Markov chain models.…”
Section: Numerical Verification Against Monte Carlo Simulationsmentioning
confidence: 96%
“…In the equations, P(z m , z n , θ i ) is the probability for the photon that starts its propagation at z m with the propagating direction of θ i and finishes at z n during a specific time step; P(θ i , θ j , n) is the probability for the photon that propagates in the direction of θ i , snth layer, and then propagates in the new direction of θ j ; and Γ n (α) is the phase function in the nth layer. The implications of Equations ( 2)-( 4) have been introduced elsewhere [15][16][17][18], and we will briefly introduce these equations. Equation ( 2) describes the transition probability T from one state (z m , θ i ) to another state (z n , θ j ).…”
Section: Mathematical Formation Of the Time-based Markov Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, it is often faster to evaluate the first relation and truncate the series at a finite when the solution is sufficiently converged (Yang et al. 2018).…”
Section: The Radiative Transfer Equation In Slab Geometrymentioning
confidence: 99%